2017
DOI: 10.1136/vr.104042
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of reactive thrombocytosis and associated clinical conditions in dogs

Abstract: Previous studies on the underlying causes of thrombocytosis have raised scientific interest in its clinical relevance in dogs. The purpose of this study was: (1) to explore the clinical conditions associated with thrombocytosis; (2) to compare platelet counts among these conditions; and (3) to identify possible interactions with other haematological variables and associated conditions. Medical records of 195 dogs with thrombocytosis (platelet count >500×10/μL) were reviewed for signalment, complete blood count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…A total of 12,676 canine blood samples were evaluated. Of these, 573 dogs had at least one platelet count record >500 x 10³/μL, corresponding to a thrombocytosis incidence of 4.5%, which were similar to the results of other studies (5,14) . However, increased thrombocytosis incidence (7.2% and 8.5%) was reported (4,12) , which could be because platelets were counted using different procedures, including manual hemocytometer counting, blood smear estimate, automated impedance, or laserinduced light scattering.…”
Section: Resultssupporting
confidence: 87%
“…A total of 12,676 canine blood samples were evaluated. Of these, 573 dogs had at least one platelet count record >500 x 10³/μL, corresponding to a thrombocytosis incidence of 4.5%, which were similar to the results of other studies (5,14) . However, increased thrombocytosis incidence (7.2% and 8.5%) was reported (4,12) , which could be because platelets were counted using different procedures, including manual hemocytometer counting, blood smear estimate, automated impedance, or laserinduced light scattering.…”
Section: Resultssupporting
confidence: 87%
“…This result is similar to the results of previous reports of canine HCC [18]. In addition, recent studies have also revealed that reactive or secondary thrombocytosis is commonly associated with neoplasias, especially carcinoma [1, 22, 32]. However, the causes of carcinoma-related thrombocytosis in dogs remain unclear; these conditions may result from paraneoplastic syndrome, as observed in human malignancies, including HCC [7, 13, 19].…”
Section: Discussionsupporting
confidence: 89%
“…1 , 2 Consumption of platelets leading to thrombocytopenia is described in a number of inflammatory and neoplastic disease processes. 3 Additionally, thrombocytosis has been described in a number of disease states, including endocrine diseases, heart disease, infectious disease, and cancers. 3 , 4 , 5 , 6 Expanded knowledge of platelets and their interactions in disease states has led to investigation into maladaptation of platelet synthesis and function.…”
Section: Introductionmentioning
confidence: 99%
“… 3 Additionally, thrombocytosis has been described in a number of disease states, including endocrine diseases, heart disease, infectious disease, and cancers. 3 , 4 , 5 , 6 Expanded knowledge of platelets and their interactions in disease states has led to investigation into maladaptation of platelet synthesis and function. One maladaptation is paraneoplastic thrombocytosis, in which tumor production of inflammatory mediators or stimulatory molecules leads to an increase in platelet count, which may aid in metastasis and tumor evasion of the immune system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation